Translation Ethnography: A Case Study of Translation History in the Marijampole Region of Southwest Lithuania - Vilkienė, Vida (Vertimo studijos, 2021)
The cultural and geopolitical reasons that led the Marijampole region of southwestern Lithuania to become a cradle of translation activities are discussed in the paper. Brief references regarding the cultural elite, and cultural and political activists starting from the middle of the 19th century are provided: they deserve consideration because of different incentives and goals inherent in their lifetime activities and their input into translation. Many writers of the Marijampole region who were born, educated and lived there would translate from different European languages to introduce the culture of the world to Lithuanians and encourage them to be proud of their own identity. Some of them, especially linguists, pioneered theories of translation. They conducted research on translation and analyzed various issues of translated literature. Although the article limits itself to just one region, it deals with the importance of translation activities as a strengthening factor of the nation-state and preservation of its language.
Keywords: translation; translation ethnography; development; history